Near-thermal equilibrium growth of SiC by physical vapor transport - Hundhausen, Martin; et al. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 1999)
Silicon carbide single crystals of the 4H-, 6H- and 15R- polytype are grown by using physical vapor transport (PVT). The crystal growth is performed at conditions where the growth chamber is close to thermal equilibrium. Micropipe-free growth of 6H-SiC on both the C- and Si-face of a 6H-SiC seed is demonstrated. 4H/15R bulk material has been grown on 4H-/15R-seeds, respectively. The growth of 4H-/15R-SiC can not yet be stabilized for the entire boule. Micropipe generation is observed in the neighborhood of polytype transitions, where Raman spectroscopy reveals internal stress. Nitrogen donor concentrations and concentrations of the compensation range from 5.9 × 1017 to 1.5 × 1018 cm-3 and from 3 × 1017 to 6 × 1017 cm-3, respectively. The maximum of the electron Hall mobility is about 200 cm2 (Vs)-1 (6H-SiC) and 300 cm2 (Vs)-1 (4H- and 15R-SiC). © 1999 Elsevier Science S.A. All rights reserved.
UnivIS-Import:2015-04-14:Pub.1999.nat.dphy.IAP.LAP.nearth
Keywords: Defects; Electronic properties; Raman; Silicon carbide; Sublimation growth